(untitled) (Global Journal of Medical Research, 2020)
Background and objectives: Tonsillectomy is the most common surgical procedure in specialty of otorhinolaryngology. Therefore there are frequent premises regarding this procedure to be improved from different aspects, indications, time of surgery, techniques, safety measures, and postoperative care. Hence the tonsils and peritonsillar tissues are highly vascular zone that supplied by direct branches of external carotid artery thus the post-tonsillectomy bleeding remains one of significant issues in relation to this widely performed procedure. The post-tonsillectomy bleeding needs frequently to be postulated for its incidence, prevalence, etiology, predisposing factors, management and prevention. This subject constitutes one of most risky aspects that increase wariness of the surgeons regarding this commonly conducted procedure. Although there are huge numbers of presentative literatures coming from American as well as western institutes that tried to put guidelines for purpose of prevention and management of post-tonsillectomy bleeding but broadly at our middle-east region and locally at our Libyan society we found for some extent difficulties to apply all these guidelines. For this reason this issue has been take the wider spectrum of ENT surgeons’ concentration, discussions, and researches.